Implementasi Keperawatan Tuberkulosis Paru dengan Bersihan Jalan Napas Tidak Efektif dan Nutrisi Tidak Seimbang: Kurang dari Kebutuhan Tubuh - Muhamad Rofi’i (Holistic Nursing and Health Science, 2021)
Introduction: Several nursing implementations do not match with nursing intervention classification. This situation requires further study to prove it. This study aims to describe nursing implementations on tuberculosis patients with airway clearance ineffective and imbalance nutrition: less than body requirement. Methods: This study was a quantitative observational descriptive study. Data were collected by observing nursing implementation documentations during two months. The research variable was nursing implementation in pulmonary tuberculosis patients. The sampling technique was purposive sampling.Results: Most of the implementation carried out by nurses in the diagnosis of ineffective airway clearance was providing oxygen (58.1%) and the second order was recommending sputum in the pot (10,5%). Most nursing implementation in diagnosis imbalance nutrition: less than body required was to educate the diet (85.7%), and the smallest is to recommend eating that is not spicy (1.2%). Conclusion: The most implementation that nurses do to overcome the diagnosis of ineffective airway clearance was giving oxygen to the patient. While the most implementation that nurses do in diagnosis imbalance nutrition: less than body required was educate the patient's diet. Interventions carried out by nurses are activities of the intervention, not nursing interventions. Further studies are required to improve nurses’ skills to implement according to standards.